The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/schbul/sbaa137
|View full text |Cite
|
Sign up to set email alerts
|

Excess Mortality and Life-Years Lost in People With Schizophrenia and Other Non-affective Psychoses: An 11-Year Population-Based Cohort Study

Abstract: Psychotic disorders are associated with premature mortality, but research was primarily based on Western countries and rarely examined non-affective psychoses other than schizophrenia (ONAP). This population-based cohort study investigated excess mortality in 46 896 schizophrenia and 20 651 ONAP patients between January 2006 and December 2016 in Hong Kong (HK), by estimating all-cause and cause-specific standardized mortality ratios (SMRs), and life-years lost (LYLs), a recently developed, more precise reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…With regard to lifestyle, diet plays a fundamental role in preventing several diseases that are especially common in patients with schizophrenia, including obesity or being overweight, hypertension, and cardiovascular disease [ 30 , 31 , 32 , 33 , 34 ]. The situation produced by the COVID-19 pandemic set off alarms about the possible negative impact of social distancing measures and movement restrictions on the nutritional health of the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to lifestyle, diet plays a fundamental role in preventing several diseases that are especially common in patients with schizophrenia, including obesity or being overweight, hypertension, and cardiovascular disease [ 30 , 31 , 32 , 33 , 34 ]. The situation produced by the COVID-19 pandemic set off alarms about the possible negative impact of social distancing measures and movement restrictions on the nutritional health of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This result is especially alarming if we also consider that obesity or being overweight are risk factors for the development of cardiovascular diseases, which represent one of the main causes of premature death in patients with schizophrenia [ 27 , 31 , 33 ]. In line with this data, the results of a recent study carried out during the pandemic in patients with mental disorders found a higher body mass index compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…CDARS generates unique, anonymised patient identifiers to protect privacy and to link all medical records. This database has been used to conduct high-quality population-based studies on various psychiatric disorders including schizophrenia and other psychoses (Chang et al ., 2020 ; Yung et al ., 2020 , 2021 ; Chan et al ., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Excess life-years lost (LYLs) for all-cause mortality were also calculated as a complementary mortality measure. Following the method adopted in previous research for LYL estimation (Andersen, 2017 ; Erlangsen et al ., 2017 ; Plana-Ripoll et al ., 2019 ; Yung et al ., 2021 ), we first computed average life expectancy at first-recorded diagnosis of bipolar disorder (as a proxy for age of onset), which takes into account varying ages at illness onset. Life expectancies of patients were calculated for every age at diagnosis from 15 years until a set upper-age limit (95 years in the current study).…”
Section: Methodsmentioning
confidence: 99%
“…On average people with schizophrenia spectrum psychosis die 15–20 years earlier than the rest of the general population ( Reininghaus et al, 2015 ). Although smoking and cardiometabolic risk factors disproportionately affect those with psychosis increasing the risk of natural causes of death, suicide rates among people with psychosis are also significantly greater than the general population ( Yung et al, 2020 ). One in every 20 individuals with schizophrenia will die by suicide ( Palmer et al, 2005 ), twenty times the United Kingdom (UK) national rate ( Reininghaus et al, 2015 ), and equivalent to 4.3 deaths per 1000 person-years ( Bjorkenstam et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%